2012
DOI: 10.1016/j.jams.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Microgranules into Cell-like Structures in Fertilized Chicken Eggs: Hypothesis for a Mitosis-free Alternative Pathway

Abstract: According to Bonghan Kim's theory of anatomical reality for acupuncture meridians, DNA microgranules known as Sanals are key functional components in the primo vascular system (formerly the Bonghan system). To investigate this issue, we developed a new system, an incubator bound to a phase-contrast microscope, in which we cultivated and then observed for 10 hours microgranules taken from 3-day-old chick embryos and from blastoderms of fertilized chicken eggs. With this system, we found that, over time, the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…First, Lee et al attempted to demonstrate that a sanal exists and has DNA inside and grows by a budding process [36]. Then Lee et al [37] observed about 1  μ m sized extracellular vesicles, which seem quite similar to what Bonghan Kim reported in his paper [4], that cell-like structures with DNA signal in a concentric growth pattern grew in fertilized eggs [37]. In order to observe the fusion of eDNA microvesicles, Lee et al developed a special incubating chamber equipped with a microscope, for simultaneous incubation and observation of extracellular DNA vesicles [37].…”
Section: Hypothetical Functions Of the Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Lee et al attempted to demonstrate that a sanal exists and has DNA inside and grows by a budding process [36]. Then Lee et al [37] observed about 1  μ m sized extracellular vesicles, which seem quite similar to what Bonghan Kim reported in his paper [4], that cell-like structures with DNA signal in a concentric growth pattern grew in fertilized eggs [37]. In order to observe the fusion of eDNA microvesicles, Lee et al developed a special incubating chamber equipped with a microscope, for simultaneous incubation and observation of extracellular DNA vesicles [37].…”
Section: Hypothetical Functions Of the Pvsmentioning
confidence: 99%
“…Lee et al [37] hypothesize that if cell fusion is the basis of life formation, the fusion of eDNA microvesicles, named “microzymas” and “sanal,” should also occur at the subcellular level [37]. …”
Section: Pvs: a Network System For The Subcellular Level Activitiesmentioning
confidence: 99%
“…An optical device in an incubation chamber was developed based on the setup used in our previous research showing the growth of extracellular vesicles to form cell-like structures (Lee et al, 2012c). The new setup was equipped with a transparent cover under an objective lens.…”
Section: Setup For Observationmentioning
confidence: 99%
“…For incubation and observation of the specimen, we used white petrolatum, which is used for skin protection, (Vijon, USA) on the slide glass. Detailed descriptions of the experiments and equipment are given in our previous work (Lee et al, 2012c).…”
Section: Setup For Observationmentioning
confidence: 99%
See 1 more Smart Citation